التفسير التحليلي للآيات (1-8) من سورة الأنعام: دراسة نموذجية - Mannan, Anamul Hoque Abdul (Asian Journal of Islamic Studies and Da'wah, 2025)
This research addresses a type of interpretation: analytical interpretation. This study aims to uncover the secrets of the close connection between the Qur'anic verses in the blessed Surah Al-An'am, from verse (1) to verse (8), and the gems and pearls they contain, using an analytical and inductive approach. Surah Al-An'am is one of the Meccan surahs that addresses the fundamentals of religion, including monotheism, the message, and resurrection. It was given this name because the word "Al-An'am" appears in it. A thing may be named by its part, and this naming is of a similar nature. The aforementioned verses aim to prove the oneness of God, glory be to Him, refute the beliefs of the polytheists, and call for belief in resurrection and judgment. This modest study has reached several conclusions, the most important of which are: God's verses demonstrate His monotheism and His power in creation and management; demonstrate the polytheists' disregard for the clear signs and miracles; and refute the polytheists' arguments and demonstrate their persistence in disbelief and denial.